Towards Bioleaching of a Vanadium Containing Magnetite for Metal Recovery - Bellenberg, Sören; Turner, Stephanie; Seidel, Laura; van Wyk, Nathan; Zhang, Ruichi; Sachpazidou, Varvara; Embile, Rodrigo F.; Walder, Ingar; Leiviskä, Tiina; Dopson, Mark (Frontiers in Microbiology, 2021)
Vanadium – a transition metal – is found in the ferrous-ferric mineral, magnetite. Vanadium has many industrial applications, such as in the production of high-strength low-alloy steels, and its increasing global industrial consumption requires new primary sources. Bioleaching is a biotechnological process for microbially catalyzed dissolution of minerals and wastes for metal recovery such as biogenic organic acid dissolution of bauxite residues. In this study, 16S rRNA gene amplicon sequencing was used to identify microorganisms in Nordic mining environments influenced by vanadium containing sources. These data identified gene sequences that aligned to the Gluconobacter genus that produce gluconic acid. Several strategies for magnetite dissolution were tested including oxidative and reductive bioleaching by acidophilic microbes along with dissimilatory reduction by Shewanella spp. that did not yield significant metal release. In addition, abiotic dissolution of the magnetite was tested with gluconic and oxalic acids, and yielded 3.99 and 81.31 % iron release as a proxy for vanadium release, respectively. As a proof of principle, leaching via gluconic acid production by Gluconobacter oxydans resulted in a maximum yield of 9.8 % of the available iron and 3.3 % of the vanadium. Addition of an increased concentration of glucose as electron donor for gluconic acid production alone, or in combination with calcium carbonate to buffer the pH, increased the rate of iron dissolution and final vanadium recoveries. These data suggest a strategy of biogenic organic acid mediated vanadium recovery from magnetite and point the way to testing additional microbial species to optimize the recovery.